Assessment of Local Key Sectors in a Triple-Layer Spatial System - Eveline van Leeuwen; Yoshifumi Ishikawa; Peter Nijkamp (Tinbergen Institute, 2013)
This article addresses the differentiated impacts of various sectors and branches in a multi-layer regional system. As a case-study the Cairngorms National Park (CNP) in Scotland is used. In this area, policy makers ”at different administrative levels” strongly emphasize the need for new sustainable economic development. We use a novel combination of stakeholder analysis with household questionnaires and interregional input-output analysis to define the most important local key-sectors as carriers for local sustainability. The methodological vehicle employed is based on microsimulation. This paper demonstrates how, even for small areas such as the CNP in Scotland, survey information combined with secondary data and existing input-output tables can be integrated into a useful policy tool.
Keywords: R1; 330; Input-output analysis; microsimulation; key-sectors; Scotland; multi-regional